2008
DOI: 10.1002/dev.20305
|View full text |Cite
|
Sign up to set email alerts
|

Social play in crested and japanese macaques: Testing the covariation hypothesis

Abstract: Most studies about social play have focused on its function in aiding socialization. It is not known whether play patterns vary by species according to specific adult social relationships. To test whether there is covariation between the form of play interactions and adult relationships, we studied social play in Japanese macaques (Macaca fuscata) and crested macaques (Macaca nigra). Comparative studies have shown that whereas low levels of tolerance and strict hierarchies characterize Japanese macaques, crest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 36 publications
6
55
0
1
Order By: Relevance
“…All of our study species showed a negative relationship between scores on the Sociability personality dimension and age. This relationship again reflects the playfulness component of Sociability, one of the most important components of this dimension; it is well known that young primates in general play more than adults (Petit et al 2008), and this has been demonstrated for other Macaca spp. (Caine and Mitchell 1979;Ciani et al 2012) and S. sciureus (Baldwin 1969;Biben, 1998).…”
Section: Validity Of Personality Assessmentsmentioning
confidence: 93%
See 1 more Smart Citation
“…All of our study species showed a negative relationship between scores on the Sociability personality dimension and age. This relationship again reflects the playfulness component of Sociability, one of the most important components of this dimension; it is well known that young primates in general play more than adults (Petit et al 2008), and this has been demonstrated for other Macaca spp. (Caine and Mitchell 1979;Ciani et al 2012) and S. sciureus (Baldwin 1969;Biben, 1998).…”
Section: Validity Of Personality Assessmentsmentioning
confidence: 93%
“…Male M. nigra and S. sciureus also scored higher on Sociability than females, which probably reflects the playfulness component of Sociability because males at all ages generally spend more time playing than females, and females withdraw from play behavior much earlier than males as they begin to travel, forage, and rest more with adult females (Baldwin 1969;Biben 1998;Petit et al 2008). All of our study species showed a negative relationship between scores on the Sociability personality dimension and age.…”
Section: Validity Of Personality Assessmentsmentioning
confidence: 95%
“…In some cercopithecine species, the use and structure of particular facial expressions can converge as a function of their species‐typical baseline levels of tolerance and affiliation (Thierry et al ., ; Petit, Bertrand & Thierry, ). For example, in crested macaques ( Macaca nigra ), mandrills ( Mandrillus sphinx ) and geladas, the FPF is not a more intense version of PF but derives from the convergence between PF and the silent‐bared teeth display, a facial expression used for affinitive purposes (van Hooff & Preuschoft, ; Bout & Thierry, ).…”
Section: Rt Communication Patterns Exclusive To Playmentioning
confidence: 99%
“…Differences in social structure, namely social tolerance among females, have been linked to differences in e.g. play behaviour [37], [38], patterns of migration [39] and group decision-making [7], [8]. The lack of age and rank effects on the frequency of movement initiation and the lacking relation between social bonding patterns and the joining order observed in Tonkean macaques has been suggested to result from their high degree of social tolerance and the lack of kin preference in social behaviour.…”
Section: Introductionmentioning
confidence: 99%